2012
DOI: 10.1063/1.4745016
|View full text |Cite
|
Sign up to set email alerts
|

Photon recycling across a ultraviolet-blocking layer by luminescence in polymer solar cells

Abstract: UV-blocking layers can increase the long term stability of organic solar cell devices; however, they limit the amount of light that can be utilized for energy conversion. We present photon recycling and down-conversion via a luminescent layer across a UV-blocking TiO2 layer. Our results show that the use of an additional UV-blocking layer does not necessarily reduce the overall efficiency of organic solar cells, since the loss in photocurrent due to the UV-absorption loss can be partially compensated using hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…[180] shelf lifetime 94 6000 pentacene:PCBM Al 2 O 3 film [181] shelf lifetime 80 500 P3HT:PCBM commercial barrier foil [53] outdoor 40 1000 P3HT:PCBM polyurethane [186] outdoor 40 over 3000 inverted P3HT:PCBM inorganic/organic [22] shelf lifetime 50 6000 P3HT:PCBM glass sheet [207] illumination 96 120 inverted P3HT:PCBM glass sheet [26] illumination 50 5000 P3HT:PCBM glass sheet [129] illumination 80 4000 PCDTBT/PC 70 BM and P3HT:PCBM PET with side protection [210] illumination almost 100 800 P3HT:PCBM glass sheet [149] illumination over 50 4700 inverted P3HT:PCBM glass sheet [208] illumination www.chemphyschem.org These encapsulationt echniques have led to the development of OPV devices with increased stability and lifetime.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[180] shelf lifetime 94 6000 pentacene:PCBM Al 2 O 3 film [181] shelf lifetime 80 500 P3HT:PCBM commercial barrier foil [53] outdoor 40 1000 P3HT:PCBM polyurethane [186] outdoor 40 over 3000 inverted P3HT:PCBM inorganic/organic [22] shelf lifetime 50 6000 P3HT:PCBM glass sheet [207] illumination 96 120 inverted P3HT:PCBM glass sheet [26] illumination 50 5000 P3HT:PCBM glass sheet [129] illumination 80 4000 PCDTBT/PC 70 BM and P3HT:PCBM PET with side protection [210] illumination almost 100 800 P3HT:PCBM glass sheet [149] illumination over 50 4700 inverted P3HT:PCBM glass sheet [208] illumination www.chemphyschem.org These encapsulationt echniques have led to the development of OPV devices with increased stability and lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…UV-blocking layers can increase the long-term stabilityo fo rganic solar-cell devices by filtering out UV radiation. [180] In the same work, al uminescent layer was also inserted on top of the UV-blocking layer to enablep hoton recycling, which thusenhanced devicep erformance. [179] In P3HT:PCBM devices with an ormala rchitecture, TiO 2 -SiO x layers have been successfully used to block UV radiation.…”
Section: Low-cost Encapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The organic nature of the constituent layers make the OPV devices very sensitive to photooxidation, which takes place upon UV radiation and ingress of oxygen and water into the solar cell device [2,3]. In order to overcome this problem, different approaches are being investigated: development of intrinsically more photochemically stable materials [4][5][6], optimization of encapsulation [7][8][9], and implementation of getter materials and oxygen, humidity [2,10,11], and UV blocking layers [12][13][14]. In this study, we discuss the possibilities of stabilizing OPV devices using small molecule materials as stabilizing additives and compare the working mechanisms of different classes of commercially available materials.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the potential for efficiency and stability enhancements via LDS layers have been reported in a wide range of PV technologies, including Dye Sensitised Solar Cells (DSSCs) [9], there are only a limited number of studies that have been carried out on OPV materials [10] and devices [11,12,13]. In particular, Sloff et al and Engmann et al have reported promising results that show a photocurrent improvement by applying LDS layers in OPVs, but the stability issue was not addressed.…”
Section: Introductionmentioning
confidence: 99%